A 1.8-GHz Spur-Cancelled Fractional-N Frequency Synthesizer With LMS-Based DAC Gain Calibration - Gupta, M.; Bang-Sup Song (IEEE journal of solid-state circuits, 2006)
A 1.8-GHz wideband DeltaSigma fractional-N frequency synthesizer achieves the phase noise performance of an integer-N synthesizer using a spur-cancellation digital-to-analog converter (DAC). The DAC gain is adaptively calibrated with a least-mean-square (LMS) sign-sign correlation algorithm for better than 1% DAC and charge pump (CP) gain matching. The proposed synthesizer phase-locked loop (PLL) is demonstrated with a wide 400-kHz loop bandwidth while using a low 14.3-MHz reference clock, and offers a better phase noise and bandwidth tradeoff. Using an 8-bit gain-calibrated DAC, DeltaSigma-shaped divider ratio noise is suppressed by as much as 30 dB. The second-order DeltaSigma fractional-N PLL exhibits in-band and integrated phase noises of -98 dBc/Hz and 0.8deg. The chip, fabricated in 0.18-mum CMOS, occupies 2 mm 2 , and consumes 29 mW at 1.8-V supply. The spur cancellation and correlation function consumes 30% additional power